Endophyte infection, nutrient status of the soil and duration of snow cover influence the performance of meadow fescue in sub-artic conditions - Wäli, Piippa; Helander, Marjo; Nissinen, Oiva; Lehtonen, Päivi; Saikkonen, Kari (Grass and Forage Science, 2008)
v 2008 ok pka